The Effect of Discovery Learning Strategy and Learning Motivation on Learning Outcomes of Islamic Education Elementary School of Number 106190 Kotapari, Pantai Cermin District, North Sumatra - Abd. Mukti; Zulheddi; Elfi Syahroini (Britain International of Linguistics Arts and Education (BIoLAE) Journal, 2020)
This study aims to determine: (1) differences in student learning outcomes taught by using the discovery learning strategy with student learning outcomes taught by expository strategies, (2) differences in the learning outcomes of students who have high motivation and low motivation by using learning learning strategies , (3) differences in learning outcomes of students who have high motivation and low motivation using expository learning strategies, and (4) the interaction between the effects of learning strategies and motivation on student learning outcomes. The research method used is quantitative with a quasi-experimental model of factorial design 2 x 2. The research sample is 1 class for discovery learning strategy learning and 1 class is expository learning strategy. Data collection instruments are tests and questionnaires. The data analysis technique is a two-way analysis of variance. The difference in value between the experimental class and the control class is not significant enough so that it can be interpreted that there cannot be a significant difference in student learning outcomes between the experimental class and the control class.